Characterisation of materials: determining density using X-ray microtomography. (January 2015) - Davis, G. R.; Evershed, A. N. Z.; Mills, D.
<x content-type="archive" xml:space="preserve">Abstract</x> The authors have previously published a method of beam hardening correction for X-ray microtomography that allows accurate determination of mineral concentration in hard tissue. This uses a multi-element calibration carousel for making experimental X-ray attenuation measurements to optimise the parameters in a model of X-ray transmission and detection. From this, a calibration curve is generated to convert the X-ray polychromatic X-ray projection data to that which would be expected with monochromatic X-rays. Furthermore, the calibration curve can be modified according to the known composition of the specimen. Here, this is tested using different materials to assess its accuracy in determining their density. Generally, errors in density of around 1–2% were obtained. When modelling the conventional use of an aluminium step wedge, much larger errors are seen. The technique can be used to measure and map density or concentration in cases where this would be difficult with other methods.